2004
DOI: 10.1007/s00267-003-3080-9
|View full text |Cite
|
Sign up to set email alerts
|

Deflector Designs for Fish Habitat Restoration

Abstract: Paired current deflectors are structures that are installed on each bank of a river to locally reduce the width of the channel, thereby creating flow acceleration and promoting scouring. These instream habitat structures have been used extensively in restoration projects to create pool habitat for fish, but there are many discrepancies in deflector design recommendations in terms of orientation, height, and length. Our objectives were to (1) examine how the angle, height, and length of paired deflectors affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 1 publication
2
34
0
Order By: Relevance
“…Thompson [8] conducted flume experiments on the effect of scour pools at low and high deflectors, and concluded that high deflectors have been proven much more useful to create scour pool habitat. Some previous research reported that the orientation of deflectors is associated with the volume of scour pools [3,7,9]. Maximum scour was observed at spur dikes oriented perpendicular to the flow [3].…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Thompson [8] conducted flume experiments on the effect of scour pools at low and high deflectors, and concluded that high deflectors have been proven much more useful to create scour pool habitat. Some previous research reported that the orientation of deflectors is associated with the volume of scour pools [3,7,9]. Maximum scour was observed at spur dikes oriented perpendicular to the flow [3].…”
Section: Introductionmentioning
confidence: 96%
“…There are a lot of instream habitat structures such as deflectors, rock vanes, and spur dikes. A usual design of instream habitat structure is the use of flow deflectors, which are recognized as one of the best tools for habitat restoration techniques [3,4]. Deflectors provide various flow conditions by constricting and diverting the water, thereby enhancing ecosystem diversity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Velocities were also higher than for the first set of experiments, in order to examine the combined effect of increasing flow stage and velocity. Bed shear stress was calculated from the turbulent kinetic energy (TKE) approach, which has proved more accurate in a complex flow field than other methods based on mean velocities (Biron et al [11]). The 3D CFD model Phoenics was used to run simulations of the flow field at the Nicolet River for low and high flow conditions.…”
Section: Methodsmentioning
confidence: 99%
“…The impact of increasing both water stage and velocities around deflectors is not clear because many laboratory experiments have used constant flow intensity conditions for various overtopping ratios (e.g. Kuhnle et al [10]; Biron et al [11,12]). …”
Section: Introductionmentioning
confidence: 99%